n = 1 ∑ 4 8 n n 2 ( n + 1 ) + n ( n + 1 ) 2 ( n − 1 ) ! ( n 3 − n − 1 )
If the summation above equals to S , find the value of S + 1 4 8 ! .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Did the same way
Did the exact same
Let us demystify the expression to be summated
n n 2 ( n + 1 ) + n ( n + 1 ) 2 ( n − 1 ) ! [ n 3 − n − 1 ]
Taking n ( n + 1 ) common from the denominator
⇒ n ( n + 1 ) [ n n + n + 1 ] ( n − 1 ) ! [ n 3 − n − 1 ]
⇒ n ( n + 1 ) ( n − 1 ) ! [ n n − n + 1 ]
⇒ n ( n + 1 ) n ( n − 1 ) ! n − n ( n + 1 ) n + 1 ( n − 1 ) !
⇒ n + 1 n ! − n ( n − 1 ) !
This looks to be the n t h term of the summation given.
S = n = 1 ∑ 4 8 n + 1 n ! − n ( n − 1 ) !
S = 2 1 ! − 1 0 ! + 3 2 ! − 2 1 ! + … + 4 9 4 8 ! − 4 8 4 7 !
S = 7 4 8 ! − 1
Required answer is
S + 1 4 8 ! = 7 4 8 ! − 1 + 1 4 8 ! = 4 8 ! 4 8 ! 7 = 7
Problem Loading...
Note Loading...
Set Loading...
S = n = 1 ∑ 4 8 n n 2 ( n + 1 ) + n ( n + 1 ) 2 ( n − 1 ) ! ( n 3 − n − 1 )
= n = 1 ∑ 4 8 ( n n 2 ( n + 1 ) + n ( n + 1 ) 2 ) ( n n 2 ( n + 1 ) − n ( n + 1 ) 2 ) ( n − 1 ) ! ( n 3 − n − 1 ) ( n n 2 ( n + 1 ) − n ( n + 1 ) 2 )
= n = 1 ∑ 4 8 n 4 ( n + 1 ) − n ( n + 1 ) 2 ( n − 1 ) ! ( n 3 − n − 1 ) ( n n 2 ( n + 1 ) − n ( n + 1 ) 2 )
= n = 1 ∑ 4 8 n ( n + 1 ) ( n 3 − n − 1 ) ( n − 1 ) ! ( n 3 − n − 1 ) ( n n 2 ( n + 1 ) − n ( n + 1 ) 2 )
= n = 1 ∑ 4 8 n ( n + 1 ) ( n − 1 ) ! ( n 2 n + 1 − ( n + 1 ) n )
= n = 1 ∑ 4 8 n + 1 n ! n + 1 − n ( n − 1 ) ! n
S = 4 9 4 8 ! 4 9 − 1 0 ! 1 = 7 4 8 ! − 1
⟹ S + 1 4 8 ! = 7